Natural variation of BSK3 tunes brassinosteroid signaling to regulate root foraging under low nitrogen - Zhongtao Jia (Nature Portfolio, 2019)
Plant roots elongate under mild nitrogen deficiency as part of a foraging response that facilitates nutrient uptake. Here the authors show that natural variation in this response among Arabidopsis accessions depends on the brassinosteroid (BR) signaling kinase BSK3, which can enhance BR sensitivity and root growth.